CHINESE HERBAL MEDICINE SHENQI DETOXIFICATION GRANULE INHIBITS FIBROSIS IN ADENINE INDUCED CHRONIC RENAL FAILURE RATS - Peng, Min; Cai, Pingping; Ma, Hongbo; Meng, Hongyan; Xu, Yuan; Zhang, Xiaoyi; Si, Guomin (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
The progressive fibrosis accompanies all chronic renal disease, connective tissue growth factor (CTGF,) and platelet-derived growth factor-B, (PDGF-B,) play important roles in extra-cellular matrix abnormal accumulation, while endothelin -1 (ET-1) nitric oxide (NO,) are related to endothelial dysfunction, which mediates the progression of renal fibrosis. Shenqi Detoxification Granule (SDG), a traditional Chinese herbal formula, has been used for treatment of chronic renal failure in clinic for many years. In order to evaluate the efficacy, and explore the mechanism of SDG to inhibit the progression of renal fibrosis, study was carried out using the adenine-induced Wister rats as the CRF model, and losartan as postive control drug. Levels of serum creatinine [Scr], and blood urea nitrogen (BUN), albumin (ALB), 24hrs, urine protein (24hUP), triacylglycerol (TG), and cholesterol (CHO), together with ET-1, and NO were detected. Pathological changes of renal tissues were observed by HE, staining. In addition, CTGF and PDGF-B expression were analyzed by immuno-histo-chemistry. The results indicated that SDG can effectively reduce Scr, BUN, 24hUP, TG, and CHO levels, increase ALB levels, inhibit renal tissue damage in CRF rats, and the mechanism maybe reduce PDGF-B, CTGF expression and ET-1/NO. Shenqi Detoxification Granule is a beneficial treatment for chronic renal failure.